Foundations of Computational Mathematics, Santander 2005 - Pardo, L. M. (Luis M.); Pinkus, Allan; Suli, Endre; Todd, Michael J. (London Mathematical Society lecture note series, 2006)
Surveys and summaries of latest research in numerical analysis, optimization, computer algebra and scientific computing.